Lupins: Their Unique Nutritional and Health-Promoting Attributes - Johnson, Stuart; Clements, J.; Villarino, C.; Coorey, R. (2017)
© 2017 Elsevier Ltd. All rights reserved. Lupins Lupinus spp, Fabaceae (legume) family] have high protein and high dietary fiber seeds of great, but under-exploited, potential for human nutrition. Evolving in Central America and the Mediterranean, this "ancient grain" once provided food for the indigenous civilizations. Lupin lost favor as a human food in modern times however, its role as a nitrogen-fixing crop in rotation with cereals to sustain soil fertility and crop yields meant it has not been forgotten. Western Australia produces the majority of the world's lupin seeds, mostly low alkaloid sweet lupin, primarily as animal feed. Recently, industry and consumer interest in lupin as food has been fueled by studies highlighting human health benefits of its consumption. However, lupin allergy has been reported, and mandatory allergen labeling of lupin is now required in several countries. Research is now required to better understand lupin functionality in foods to identify a greater range of applications.